A Cell-Based Metabonomics Approach to Investigate the Varied Influences of Chrysophanol-8-O-β-D-Glucoside With Different Concentrations on L-02 Cells - Meichen Liu; Xiaohong Gong; Yunyun Quan; Yimeng Zhou; Yunxia Li; Cheng Peng (Frontiers Media S.A., 2019)
In this study, the effects of different concentrations of chrysophanol-8-O-β-D-glucoside (C-8-O-β-D-glu) on L-02 liver cells were analyzed by high content analysis (HCA) and metabonomics to explore the potential mechanism involved. The results showed that low concentrations (12 and 24 μM) of C-8-O-β-D-glu increased the cells viability significantly, while high concentration (96 μM) showed significant cytotoxicity on L-02 cells. HCA was applied to analyze the changes of nuclei and mitochondria after the cells being exposed to C-8-O-β-D-glu for 24 h. The results showed high concentration (96 μM) of C-8-O-β-D-glu significantly reduced the number of living cells, increased average nucleus area, DNA content and mitochondrial membrane potential (MMP). Then non-target metabonomics was carried out to identify potential biomarkers and metabolic pathways of L-02 cells impacted by C-8-O-β-D-glu. Eleven important potential biomarkers associated with four metabolic pathways were identified in this analysis. Dysregulation of alanine, aspartate and glutamate metabolism were observed in both LCG and HCG. In addition, low concentration (24 μM) of C-8-O-β-D-glu would impact arginine and proline metabolism. High concentration (96 μM) of C-8-O-β-D-glu would impact phenylalanine metabolism and beta-alanine metabolism. Alanine, aspartate and glutamate metabolism, arginine and proline metabolism, phenylalanine metabolism, beta-alanine metabolism were involved in different effects of C-8-O-β-D-glu on L-02 cells.